2010
DOI: 10.1002/anie.201006781
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Halogen Bonding in Protein–Ligand Interactions

Abstract: Halogen bonding triggers activity: Increasing binding affinity was observed for a series of covalent human Cathepsin L inhibitors by exchanging an aryl ring H atom with Cl, Br, and I, which undergo halogen bonding with the CO group of Gly61 in the S3 pocket of the enzyme. Fluorine, in contrast, strongly avoids halogen bonding (see scheme). The strong distance and angle dependence of halogen bonding was confirmed for biological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
393
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(417 citation statements)
references
References 28 publications
15
393
2
4
Order By: Relevance
“…Access to the active site was prevented by inhibitors including the propeptide, which explains the crystal structures of khCL complex with the p41 fragment [11], the small molecule complexes rhCL_1 and rhCL_3 [14,29] and the proenzyme structure [10]. However, among the Q scoring, quality of alignment, which took both the alignment length and RMSD into account; Ca RMSD, root-mean-square deviation, calculated between Ca-atoms; N-align, number of matched residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to the active site was prevented by inhibitors including the propeptide, which explains the crystal structures of khCL complex with the p41 fragment [11], the small molecule complexes rhCL_1 and rhCL_3 [14,29] and the proenzyme structure [10]. However, among the Q scoring, quality of alignment, which took both the alignment length and RMSD into account; Ca RMSD, root-mean-square deviation, calculated between Ca-atoms; N-align, number of matched residues.…”
Section: Discussionmentioning
confidence: 99%
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
“…Moreover, halogenated coumpounds are often encountered in medicinal chemistry [79] and drug discovery. [80] Quantum Chemistry approaches have revealed a sigma-hole along the axis defined by the halogen atom and the acceptor. This can be studied thanks to the Molecular Electrostatic Potentials, showing the charge distribution as well as the nature of the interaction as electrostatics and charge transfer driven.…”
Section: Halogen Bondingmentioning
confidence: 99%
“…Halogen bonds form between nucleophilic acceptors, such as anions, and highly localized positive-charge density on halogen atoms appearing on the side opposite to the covalent bond [13][14][15][16][17][18][19][20][21][22] . They are most prominent with iodine atoms but occur, to a lesser extent, also with the less polarizable bromine, chlorine, and even fluorine (Fig.…”
mentioning
confidence: 99%
“…Routinely exploited in crystal engineering 14 , halogen bonds are attracting only recently some attention for rational drug design 16 , anion binding 17,18 and catalysis 19,20 . Whereas the special behaviour of molecular iodine (bp = 184 °C) has been noticed early on 21,22 , contributions of organic halogen bonds to the transport of anion across lipid bilayer membranes have been suspected last year, for the first time 13 .…”
mentioning
confidence: 99%